THE INFLUENCE OF TECHNOLOGY IN MODERN LIFE - Berdiqulova Mahbuba,; To’raxonova Rayhonoy, (TADQIQOTLAR, 2026)
ANNOTATION  Technology  plays  a  crucial  role  in  shaping  modern  society  and  influencing everyday human activities. In the 21st century, rapid technological advancement has transformed communication, education, healthcare, and economic systems. This article provides an in-depth analysis of the role of technology in different spheres of life, highlighting both its advantages and disadvantages. It also discusses the challenges associated  with  digitalization,  such  as  dependency,  cybersecurity  risks,  and psychological effects. The findings suggest that while technology enhances efficiency and global connectivity, it must used responsibly to ensure sustainable development and human well-being.